Strategy To Improve Regional Competitiveness Index Through Regional Innovation - A. A. Sri Basunari; IB Raka Suardana (Green Publisher Indonesia, 2025)
Increasing regional competitiveness is a crucial factor in supporting sustainable economic development. One key strategy for enhancing competitiveness is through regional innovation. This study aims to analyze strategies that can be implemented to improve the regional competitiveness index through innovation based on local potential. The approach used in this study is qualitative, with case study analysis of several regions that have successfully implemented regional innovation to enhance their competitiveness. The results show that the implementation of regional innovation, such as the development of superior local products, the use of digital technology, and improving the quality of human resources, can significantly increase regional competitiveness. Furthermore, collaboration between the government, the private sector, and the community also plays a crucial role in creating an innovation ecosystem that supports increased competitiveness. This study suggests the need for policies that support the development of regional innovation through the provision of adequate infrastructure, increased access to technology, and training for local human resources. Thus, regional innovation can be a key driver in increasing regional competitiveness and encouraging inclusive economic growth.